Financial Literacy: A Case Study On College Students - Mulyawan, I Putu Arya; Putri, Kompiang Martina Dinata; Pradnyadari, I Gusti Agung (Jurnal Multidisiplin Sahombu, 2025)
The term financial literacy is an individual's ability to make decisions and manage their own personal finances. Personal financial management (financial planning and control) is one form of application of financial management. For most students, college is the first time they manage their own finances without supervision from their parents. Students must be able to independently manage their finances well and must also be able to take responsibility for the decisions they have made. The method used is qualitative descriptive adjusting the opinions between researchers and informants. This method was chosen because the analysis cannot be in the form of numbers and researchers prefer to describe all phenomena that exist in society clearly. The data source in qualitative descriptive research is through questionnaires (questionnaires). The objects in this study were students who were studying at the Indonesian Business and Technology Institute (INSTIKI) located in Denpasar, Bali who were taking the Introduction to Accounting course. The research instrument in this study used the method of providing a list of questions. The population in this study were all students studying at INSTIKI. The respondents in this study were 122 people. The research results indicate that education about finance and financial literacy should be provided from an early age.